The Reasons for Chinese Students to Work Contingently in Hino Travel - Wang, Chengcheng (2013)
The research that has been conducted aims at exploring reasons for Chinese students to work contingently in a UK based company called Hino Travel. The most interesting section of this study would be the analysis and conclusion section, in which a variety of reasons mentioned by respondents will be analyzed and compared with Maslow’s hierarchy of needs. Maslow assumes that there would be hierarchical structure of needs for people’s behaviours while the result of this study does not fit Maslow’s model that different people value different things and they work contingently in Hino Travel for totally different reasons rather than following Maslow’s hierarchy. 12 interviews were conducted and the researcher herself acts as two respondents because she worked in Hino Travel for two positions at different time for different reasons; thus autoethnography works throughout the study. This is the first time for the researcher to do fieldwork, who learns a lot by trial and error; also, her lack of experience and interview skills may also lead to some limitations of this study.